Atomic origins of high electrochemical CO2 reduction efficiency on nanoporous gold. Issue 18 (3rd May 2018) - Zhang, Weiqing; He, Jia; Liu, Siyu; Niu, Wenxin; Liu, Pan; Zhao, Yang; Pang, Fangjie; Xi, Wei; Chen, Mingwei; Zhang, Wei; Pang, Su-Seng; Ding, Yi
Abstract : Low-coordinated surface atoms of nanoporous gold are responsible for high performance electrochemical CO2 reduction to CO. Abstract : First principles calculations show that gold atoms with low generalized coordination numbers possess high activity for electroreduction of CO2 to CO. Atom-resolved three-dimensional reconstruction reveals that dealloyed nanoporous gold possesses such a favourable structure characteristic, which results in a faradaic efficiency as high as 94% for CO production.